Impoliteness in the Final 2024 Indonesian Presidential Debate: Critical Discourse Analysis - Sultan Ahmad Sitepu; Putri Melinda; Mariah Teta br Ginting; Amira Tsarwah Ritonga (PT. Intelek Cendikiawan Nusantara, 2024)
Political debates are crucial in democratic societies, shaping public opinion and influencing voter decisions. The final 2024 Indonesian presidential debate, featuring candidates Prabowo Subianto, Anies Baswedan, and Ganjar Pranowo, highlighted the use of impoliteness, potentially impacting political communication dynamics. This study employs Critical Discourse Analysis (CDA) to investigate impoliteness strategies in the final 2024 Indonesian presidential debate. Data was transcribed from the KPU RI YouTube Channel, and Culpeper's impoliteness model guided the analysis of 35 instances of impoliteness. The results reveal that Prabowo Subianto and Ganjar Pranowo primarily use positive and negative impoliteness, while Anies Baswedan shows a preference for positive impoliteness. The findings highlight the candidates' use of impoliteness to assert views and critique opponents, underscoring the debate's confrontational nature.The findings indicate that the candidates employ impoliteness to assert their views and critique their opponents, highlighting the contentious nature of the debate.